The proposed railway across Newfoundland [electronic resource] : a lecture delivered in the New Temperance Hall, February 9th, 1875 - Morris, Father, 1852-1889 ([St. John's, Nfld.? : s.n.], 1875)
Electronic reproduction. Mode of access: Internet. 44